Students' Attitudes towards the Class Visit Project - Thadphoothon, Janpha (Journal of ELT, Linguistics, and Literature, 2018)
The article reports the classroom visit project experienced by 31 Thai university English major students taking a course titled Introduction to English Language Teaching (EN 391) during the first semester of the academic year 2016. The students worked in small groups, contacted the schools asking permission to observe the English classes. They observed the classroom and took notes of what they have seen and learned. They, then, in a small group, wrote a report and took turns sharing their findings in the classroom. After the completion of the project, the students were asked to answer the questionnaires with two open-ended questions addressing the experience and general impressions of the project. Data were analysed using basic descriptive statistics and content analysis. The results showed that the majority of the students had positive attitudes toward the class visit experience. They perceived it as being useful and memorable. The paper also discusses the implications of the findings.